(-12.2/7+8/9:3 1/2-2/7.5/18).3 1/2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(-12\cdot\dfrac{2}{7}+\dfrac{8}{9}:3\dfrac{1}{2}-\dfrac{2}{7}\cdot\dfrac{5}{18}\right)\cdot3\dfrac{1}{2}\)
\(=\left(-12\cdot\dfrac{2}{7}+\dfrac{8}{9}\cdot\dfrac{2}{7}-\dfrac{2}{7}\cdot\dfrac{5}{18}\right)\cdot\dfrac{7}{2}\)
\(=\left(-12+\dfrac{8}{9}-\dfrac{5}{18}\right)\cdot\dfrac{2}{7}\cdot\dfrac{7}{2}\)
\(=-\dfrac{205}{18}\cdot1\)
\(=-\dfrac{205}{18}\)
1: =72/90+65/90=137/90
2: =24/56-77/56=-53/56
3: =-7/10+4/5=1/10
4: =15/100-4/100=11/100
5: =4/6-5/6=-1/6
6: =10/40-15/40-76/40=-81/40
7: =-9/10+7/18
=-81/90+35/90=-46/90=-23/45
8: =27/90-55/90=-28/90=-14/45
9: =36/60-50/60-35/60=-49/60
10: =-4/9+5/6-3/8
=-32/72+60/72-27/72
=1/72
a: \(\left(-\dfrac{5}{6}+\dfrac{2}{5}\right):\dfrac{3}{8}+\left(\dfrac{4}{5}-\dfrac{11}{30}\right):\dfrac{3}{8}\)
\(=\left(-\dfrac{5}{6}+\dfrac{2}{5}\right)\cdot\dfrac{8}{3}+\left(\dfrac{4}{5}-\dfrac{11}{30}\right)\cdot\dfrac{8}{3}\)
\(=\dfrac{8}{3}\left(-\dfrac{5}{6}+\dfrac{2}{5}+\dfrac{4}{5}-\dfrac{11}{30}\right)\)
\(=\dfrac{8}{3}\cdot\dfrac{-25+36-11}{30}\)
=0
b: \(\left(-\dfrac{3}{4}+\dfrac{2}{5}\right):\dfrac{3}{7}+\left(\dfrac{3}{5}+\dfrac{-1}{4}\right):\dfrac{3}{7}\)
\(=\left(-\dfrac{3}{4}+\dfrac{2}{5}\right)\cdot\dfrac{7}{3}+\left(\dfrac{3}{5}-\dfrac{1}{4}\right)\cdot\dfrac{7}{3}\)
\(=\dfrac{7}{3}\left(-\dfrac{3}{4}+\dfrac{2}{5}+\dfrac{3}{5}-\dfrac{1}{4}\right)\)
\(=\dfrac{7}{3}\cdot0=0\)
c: \(\dfrac{-13}{18}\cdot\dfrac{5}{8}+\dfrac{-5}{18}\cdot\dfrac{2}{9}+\dfrac{-13}{18}\cdot\dfrac{3}{8}+\dfrac{-5}{18}\cdot\dfrac{7}{9}\)
\(=\left(-\dfrac{13}{18}\cdot\dfrac{5}{8}+\dfrac{-13}{18}\cdot\dfrac{3}{8}\right)+\left(-\dfrac{5}{18}\cdot\dfrac{2}{9}+\dfrac{-5}{18}\cdot\dfrac{7}{9}\right)\)
\(=-\dfrac{13}{18}\left(\dfrac{5}{8}+\dfrac{3}{8}\right)+\dfrac{-5}{18}\left(\dfrac{2}{9}+\dfrac{7}{9}\right)\)
\(=-\dfrac{13}{18}-\dfrac{5}{18}=-\dfrac{18}{18}=-1\)
d: Sửa đề: \(\dfrac{-11}{19}\cdot\dfrac{4}{9}+\dfrac{-8}{19}\cdot\dfrac{3}{7}+\dfrac{-11}{19}\cdot\dfrac{5}{9}+\dfrac{-8}{19}\cdot\dfrac{4}{7}\)
\(=\left(-\dfrac{11}{19}\cdot\dfrac{4}{9}+\dfrac{-11}{19}\cdot\dfrac{5}{9}\right)+\left(\dfrac{-8}{19}\cdot\dfrac{3}{7}+\dfrac{-8}{19}\cdot\dfrac{4}{7}\right)\)
\(=-\dfrac{11}{19}\left(\dfrac{4}{9}+\dfrac{5}{9}\right)+\dfrac{-8}{19}\left(\dfrac{3}{7}+\dfrac{4}{7}\right)\)
\(=-\dfrac{11}{19}-\dfrac{8}{19}=-\dfrac{19}{19}=-1\)
\(a.\left(-\dfrac{5}{6}+\dfrac{2}{5}\right):\dfrac{3}{8}+\left(\dfrac{4}{5}-\dfrac{11}{30}\right):\dfrac{3}{8}\)
\(=\left(-\dfrac{13}{30}\right):\dfrac{3}{8}+\dfrac{13}{30}:\dfrac{3}{8}\)
\(=\left[\left(-\dfrac{13}{30}+\dfrac{13}{30}\right)\right]:\dfrac{3}{8}\)
\(=0:\dfrac{3}{8}=0\)
\(b.\left(-\dfrac{3}{4}+\dfrac{2}{5}\right):\dfrac{3}{7}+\left(\dfrac{3}{5}+-\dfrac{1}{4}\right):\dfrac{3}{7}\)
\(=\left(-\dfrac{7}{20}\right):\dfrac{3}{7}+\dfrac{7}{20}:\dfrac{3}{7}\)
\(=\left[\left(-\dfrac{7}{20}+\dfrac{7}{20}\right)\right]:\dfrac{3}{7}=0:\dfrac{3}{7}=0\)
\(c.-\dfrac{13}{18}.\dfrac{5}{8}+-\dfrac{5}{18}.\dfrac{2}{9}+-\dfrac{13}{18}.\dfrac{3}{8}+-\dfrac{5}{18}.\dfrac{7}{9}\)
\(=\left(\dfrac{5}{8}+\dfrac{3}{8}\right).-\dfrac{13}{18}+\left(\dfrac{2}{9}+\dfrac{7}{9}\right).-\dfrac{5}{18}\)
\(=1.-\dfrac{13}{18}+1.-\dfrac{5}{18}=-\dfrac{13}{18}+-\dfrac{5}{18}=-1\)
\(d.-\dfrac{11}{19}.\dfrac{4}{9}+\dfrac{-8}{19}.\dfrac{3}{7}+-\dfrac{11}{19}.\dfrac{5}{9}+-\dfrac{9}{19}.\dfrac{4}{7}\)
\(=\left(\dfrac{4}{9}+\dfrac{5}{9}\right).-\dfrac{11}{19}+-\dfrac{24}{133}+-\dfrac{36}{133}\)
\(=-\dfrac{11}{19}+-\dfrac{60}{133}=-\dfrac{137}{133}\)
a) \(\frac{-5}{8}\cdot\frac{11}{3}+\frac{-5}{8}\cdot\frac{1}{3}=-\frac{5}{8}\left(\frac{11}{3}+\frac{1}{3}\right)=-\frac{5}{8}\cdot4=-\frac{5}{2}\cdot1=-\frac{5}{2}\)
b) \(\frac{2}{3}+\frac{3}{4}\cdot\frac{9}{5}=\frac{2}{3}+\frac{27}{20}=\frac{121}{60}\)
c) Tương tự câu a
d) \(\frac{1}{7}\cdot\frac{3}{8}+\frac{1}{7}\cdot\frac{5}{8}=\frac{1}{7}\left(\frac{3}{8}+\frac{5}{8}\right)=\frac{1}{7}\cdot1=\frac{1}{7}\)
\(a,\frac{-5}{8}.\frac{11}{3}+\frac{-5}{8}.\frac{1}{3}\)
\(=\frac{-5}{8}\left(\frac{11}{3}+\frac{1}{3}\right)\)
\(=\frac{-5}{8}.4\)
\(=\frac{-5}{2}\)
\(b,\frac{2}{3}+\frac{3}{4}.\frac{9}{5}\)
\(=\frac{2}{3}+\frac{27}{20}\)
\(=\frac{40}{60}+\frac{81}{60}\)
\(=\frac{121}{60}\)
\(c,\frac{-5}{7}.\frac{4}{9}-\frac{5}{9}.\frac{5}{7}\)
\(=\frac{-5}{7}\left(\frac{4}{9}+\frac{5}{9}\right)\)
\(=\frac{-5}{7}.1\)
\(=\frac{-5}{7}\)
\(d,\frac{1}{7}.\frac{3}{8}+\frac{1}{7}.\frac{5}{8}\)
\(=\frac{1}{7}\left(\frac{3}{8}+\frac{5}{8}\right)\)
\(=\frac{1}{7}.1\)
\(=\frac{1}{7}\)
Học tốt
\(a,\left(-\dfrac{4}{9}\right)\times\dfrac{3}{8}+\dfrac{1}{18}=-\dfrac{1}{6}+\dfrac{1}{18}=\dfrac{-1.3}{6.3}+\dfrac{1}{18}=\dfrac{-3+1}{18}=-\dfrac{2}{18}=-\dfrac{1}{9}\)
xem lại đề câu b
\(c,\left(\dfrac{1}{2}-\dfrac{2}{3}\right)\times\dfrac{4}{4}=\dfrac{1}{2}-\dfrac{2}{3}=\dfrac{3-4}{6}=-\dfrac{1}{6}\\ d,\dfrac{9}{7}\times\left(\dfrac{3}{7}-\dfrac{1}{2}\right)=\dfrac{9}{7}\times\left(\dfrac{3.2-7}{14}\right)=\dfrac{9}{7}\times\dfrac{-1}{14}=-\dfrac{9}{98}\)
\(F=\frac{\left(\frac{2}{5}\right)^7.5^7+\left(\frac{9}{4}\right)^9\div\left(\frac{3}{16}\right)^3}{2^7.5^2+512}\)
\(F=\frac{\left(\frac{2.5}{5}\right)^7+\left(\frac{9.16}{4.3}\right)^3}{2^7.5^2+2^9}=\frac{2^7+12^3}{2^7.5^2+2^9}=\frac{2^7+2^6.3^3}{2^7.5^2+2^9}=\frac{2^6.\left(2+3^3\right)}{2^7.\left(5^2+2^2\right)}=\frac{2^6.29}{2^7.29}\)
\(F=\frac{1}{2}\)
(-12.\(\dfrac{2}{7}\) + \(\dfrac{8}{9}\): 3\(\dfrac{1}{2}\) - \(\dfrac{2}{7}\).\(\dfrac{5}{18}\)). 3\(\dfrac{1}{2}\)
(-\(\dfrac{24}{7}\) + \(\dfrac{8}{9}\):\(\dfrac{7}{2}\) - \(\dfrac{5}{63}\)). \(\dfrac{7}{2}\)
= (-\(\dfrac{24}{7}\) + \(\dfrac{16}{63}\) - \(\dfrac{5}{63}\)).\(\dfrac{7}{2}\)
= (\(-\dfrac{216}{63}\) + \(\dfrac{16}{63}\) - \(\dfrac{5}{63}\)). \(\dfrac{7}{2}\)
= - \(\dfrac{205}{63}\). \(\dfrac{7}{2}\)
= - \(\dfrac{205}{18}\)